Proton‐sensing G protein‐coupled receptors as regulators of cell proliferation and migration during tumor growth and wound healing. Issue 2 (30th January 2017) - Weiß, Katharina T.; Fante, Matthias; Köhl, Gudrun; Schreml, Julia; Haubner, Frank; Kreutz, Marina; Haverkampf, Sonja; Berneburg, Mark; Schreml, Stephan
Abstract: Dysregulation of pH is a feature of both tumor growth and tissue repair. In tumors, microenvironmental changes, like in lactate metabolism, lead to altered intra‐ and extracellular pH (pHi, pHe ) and vice versa. In wounds, barrier disruption results in extensive variations in pHe on the wound surface. It is known that altered extracellular proton concentrations have a major impact on cell turnover and migration as well as on the metabolic activity of cells involved in tumor spread and wound closure. The proton‐sensing G protein‐coupled receptors (GPCRs) GPR4, GPR65 (TDAG8), GPR68 (OGR1) and GPR132 (G2A) are activated via a decrease in pHe and transduce this signal to molecular intracellular pathways. Based on the current knowledge, we speculate on the role of proton‐sensing GPCRs in wound healing and on their potential as mechanistic linkers of tumor growth and tissue repair.